District-Wide PBIS Team Questions Related to Using the PBIS Framework to Transition Students with Challenging Behaviors from an Alternative School to a Neighborhood School - Jolivette, Kristine; Swoszowski, Nicole C.; Josephs, Nikki L.; McDaniel, Sara C.; Ennis, Robin Parks (Journal of the American Academy of Special Education Professionals, 2012)
Students with emotional and behavioral disorders (E/BD) and those with challenging behaviors are often served in alternative education (AE) settings due to behavior that interferes with their learning and the learning of others to a degree that warrants placement outside of the traditional, neighborhood school environment. Placement in AE settings, however, is temporary as it is expected that students will transition out of the AE setting and back to their neighborhood school. Therefore, it is necessary for district schools collaborating on the transition of students between alternative and traditional placements to plan for the successful integration or reintegration of students in the least restrictive environment. This paper details the collaboration of one school district considering the use of the school-wide positive behavioral interventions and supports (SWPBIS) framework to assist in the integration and/or reintegration of students with behavioral challenges from the district alternative school to traditional middle school and vice versa.